The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jcom.12312
|View full text |Cite
|
Sign up to set email alerts
|

News Values, Cognitive Biases, and Partisan Incivility in Comment Sections

Abstract: Partisan incivility is prevalent in news comments, but we have limited insight into how journalists and news users engage with it. Gatekeeping, cognitive bias, and social identity theories suggest that journalists may tolerate incivility while users actively promote partisan incivility. Using 9.6 million comments from The New York Times, we analyze whether the presence of uncivil and partisan terms affects how journalists and news users engage with comments. Results show that partisanship and incivility increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 58 publications
3
94
1
7
Order By: Relevance
“…Beyond assessments of credibility, an abusive comment may also affect behaviors such as news-seeking by making women authors' violations of gendered social expectations (and the outlet for employing her) more salient. Previous work focuses on behaviors in the comment section: Work by Muddiman and Stroud (2017) finds that when incivility was partisan, depending on the congeniality of views expressed, users responded by recommending or flagging the comment. Similarly, other studies find that users are more likely to engage with a comment when it contains profanity (Kwon & Cho, 2017).…”
Section: Conditional Gender Effects For Abusive Commentsmentioning
confidence: 99%
“…Beyond assessments of credibility, an abusive comment may also affect behaviors such as news-seeking by making women authors' violations of gendered social expectations (and the outlet for employing her) more salient. Previous work focuses on behaviors in the comment section: Work by Muddiman and Stroud (2017) finds that when incivility was partisan, depending on the congeniality of views expressed, users responded by recommending or flagging the comment. Similarly, other studies find that users are more likely to engage with a comment when it contains profanity (Kwon & Cho, 2017).…”
Section: Conditional Gender Effects For Abusive Commentsmentioning
confidence: 99%
“…People can add to a comment section "echo chamber" with comments that further reinforce one-sided messaging (Suhay, Blackwell, Roche, & Bruggeman, 2015). Polarized content in comment sections may also amplify further polarized comments (Muddiman & Stroud, 2017). What is more, online political dialogue has a tendency to increase political polarization and extreme viewpoints (Hwang, Kim, & Huh, 2014).…”
Section: Supplemental Analysismentioning
confidence: 99%
“…Incivility is difficult to define because the decision of what is civil and uncivil is subjectively shaped (Coe et al, 2014;Herbst, 2010). Therefore, achieving consensus about where to draw the line between civil and uncivil discourse is a complex problem (Muddiman, 2017;Stryker, Conway, & Danielson, 2016). Scholars have defined incivility as the communication of disagreement combined with a dismissive, disrespectful, aggressive, or hostile tone (Coe et al, 2014;Hwang, Kim, & Kim, 2016).…”
Section: Theory: Incivility and Impolitenessmentioning
confidence: 99%
“…Researchers in social sciences have argued that using such language can be considered a violation of democratic and social norms (Muddiman & Stroud, 2017). They have, therefore, used the term 'incivility' to describe different forms of disrespectful and harmful language (e.g., Coe, Kenski, & Rains, 2014;Muddiman & Stroud, 2017). Previous studies have reported various negative effects of uncivil comments on the readers of online discussions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation